Importance of Routine Ultrasonography in Detecting Fetal Karyotype Abnormalities in Low Risk Pregnancies - Yılmaz, Zerrin; Özer, Özge; Eroğlu, Derya; Yanık, Filiz; Şahin, Feride İffet (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: The present study aims to evaluate the importance of USG findings, in estimating cytogenetic abnormality risks in pregnancies otherwise carrying low risk for aneuploidy. STUDY DESIGN: We reviewed a number of most commonly observed soft markers and structural abnormalities in pregnant women with low risk who underwent invasive prenatal diagnostic tests for USG abnormality in the period from January 2002 to December 2008, retrospectively. In 179 of all cases (9.95%), cytogenetic analysis was recommended because of USG abnormality. RESULTS: 76 patients had structural abnormalities, 95 had soft markers and 8 had intra-uterine growth restriction. We detected 12 aneuploidies in fetuses with structural abnormalities and 1 aneuploidy in fetuses with soft markers. CONCLUSION: We concluded that, although the presence or absence of soft markers can substantially modify the risk of fetal aneuploidy, one or more structural abnormalities inevitably have high risk for aneuplodies as independent factor for low-risk pregnancies.